Analisis Earned Value Pada Pembangunan Gedung Bengkel Mobil Listrik Politeknik Negeri Jember - Prasetyo, Sigit; Qordhowi , Andrian Firdaus Yusuf Al (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The construction of the Jember State Polytechnic Electric Car Workshop Building is an improvement in vocational education facilities. Obstacles in terms of mismatch between the budget plan and the implementation schedule pose a risk to cost efficiency and the timeliness of project completion. This study aims to answer the main problem formulation: how the cost and time performance of the workshop building construction project is analyzed using the Earned Value Management (EVM) method. The analysis results show that performance index values ​​such as the Cost Performance Index (CPI) and Schedule Performance Index (SPI) indicate cost efficiency but are accompanied by delays in implementation. The results of the analysis of other parameters such as CV, SV, ETC, and EAC strengthen the finding that project control still requires improvement. This study emphasizes the importance of implementing EVM as a monitoring and evaluation tool in improving the accuracy of target achievement.